1997
DOI: 10.1111/j.1600-9657.1997.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of resin monomers through human carious dentin in vitro

Abstract: The diffusion of 2-hydroxyethylmethacrylate (HEMA) and triethylene glycol dimethacrylate (TEGDMA) from light cured bonding resin-composite resin restorations through human carious dentin was investigated. Extracted human molar teeth with different degrees of caries were obtained from consenting donors. Teeth were classified into three groups according to caries severity (mild, moderate and severe) using subjective criteria. The outer carious lesions were then removed guided by a proprietary caries detector dye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 10 publications
1
33
0
3
Order By: Relevance
“…Since the caries-affected intertubular dentin is already partially demineralized and more porous, caries-affected dentin is softer than normal dentin (Ogawa & others, 1983;Hamid & Hume, 1997), and this was confirmed in this study. The intertubular dentin of caries-affected dentin is more permeable to primer than that of normal dentin.…”
Section: Discussionsupporting
confidence: 77%
“…Since the caries-affected intertubular dentin is already partially demineralized and more porous, caries-affected dentin is softer than normal dentin (Ogawa & others, 1983;Hamid & Hume, 1997), and this was confirmed in this study. The intertubular dentin of caries-affected dentin is more permeable to primer than that of normal dentin.…”
Section: Discussionsupporting
confidence: 77%
“…Measurement of such diffusion in carious teeth in vitro (Hamid and Hume, 1995) showed a moderate reduction in HEMA and TEGDMA permeability beneath mild and moderate caries but not, however, in teeth with severe caries lesions, where permeability was markedly higher. This matter requires further investiga-tion, Tagami et al (1992) reported that the hydraulic conductance of the dentin beneath caries lesions was greatly reduced compared with that of normal dentin.…”
Section: Protective Effect Of Dentinmentioning
confidence: 99%
“…In vitro methods have been recommended by the American National Standards Institute, the American Dental Association [15] for evaluation of the cytotoxicity of endodontic materials. For biomedical applications using new polymeric composite materials, it is significant to know quantively the amount of residual monomer release from the surface of the polymerized composite, because of the likely harmful effects of residual monomers on tissues [16][17][18][19][20][21][22][23][24][25]. It is well known that oxygen presence inhibits free radical polymerization of monomers of the resin.…”
Section: Introductionmentioning
confidence: 99%